Letter (copy) : Juan Expositos - Tewson, Vincent
025a-0010-001 International. HVT/AC/DT/372. 31st December, 1940. Mr. A. de Gondra, Basque Delegation, 7-8, Hobart Place, Eaton Square, LONDON, S.W.1. Dear Mr. de Gondra, JUAN EXPOSITOS. I note from your letter of the 27th of December the name of the owners of the boat on which the above Basque seamen was sunk recently and drowned. I have been in consultation with our friends of the National Union of Seamen, who informed us that as soon as you can secure the name or names of dependants or direct relatives (parents, wife or children) they are prepared to attempt to obtain compensation. The Union's difficulties will be comparatively slight if there are dependants resident in this country. One cannot, of course, speak of "dependency" if the direct relatives are living in Spain, but even in that event an attempt will be made to get the compensation although there will be additional difficulties later in respect of transfer of funds abroad. Yours sincerely, Assistant Secretary. 292/946/25a/10